Non-Linearity Cancellation of Gm-C Based DSM - Zaky, Bishoy M.; Kauffman, John G.; Conzatti, Francesco; Ortmanns, Maurits (IEEE International Symposium on Circuits and Systems proceedings, 2025)
Continuous-time (CT) Delta-Sigma-Modulators (DSMs) are widely utilized in systems requiring wide bandwidth and high resolution. While opamp-based RC integrators are favoured for their excellent linearity, they introduce low-input impedance and complicate the ADC driver. On the other side, Gm-C integrators provide high input impedance, making them more power-efficient, but they suffer from non-linearity, thereby limiting the input range. This paper explores the limitations of a specific non-linearity cancellation technique applied in DSM system-level. The principles of this technique are reviewed, and the challenges of using it at low oversampling ratio (OSR) are investigated. A theoretical analysis is presented, matching with simulation results.